CGIAR Web-of-science publications dataset - Hoyos Bertin, Nicolas; Orjuela Ramirez, Guillermo Alejandro; Esponda Bernal, Maria Del Mar; Rivera Vasco, Tatiana Carolina; Andrade López, Robert Santiago (2024)
This dataset contains all publications reported in Web of Science that belong to the CGIAR